Beyond Green : Assesing Environmental Cost Determinants - Hilery Br Ginting, Jesicha; Siagian, Valentine; Tagal Gallena Sinaga, Judith (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study aims to evaluate the fundamental factors that impact the environmental costs borne by firms included in the ESG (Environmental, Social, and Governance) index. The factors that were taken into account and analyzed include the reputation of the company, the quality of the audits, and the size of the organization in relation to environmental costs. The data collection is entailed the examination of financial records and sustainability reports. The study's population comprised companies that were indexed based on (ESG) criteria for the period of 2018–2022. The data gathering process in this study yielded a total of 285 data points for analysis, obtained from 57 different companies. The study employed a quantitative methodology using ordinary least squares and included control variables and a fixed effect. The findings of this study suggest that reputation and firm size exert a substantial impact on environmental costs, whereas the quality of audits does not have a significant effect on environmental costs. Empirically, this result shows that the better the company's reputation and the bigger the company, the higher the environmental cost spent by that company. Thus, whichever public accounting firm handles the company, will not affect the amount of environmental costs spent.